METHANOLIC FLOWER EXTRACT OF PHLOGACANTHUS THYRSIFLORUS NEES. ATTENUATES DIABETIC NEPHROPATHY IN ALLOXAN-INDUCED DIABETIC MICE - Bora, Jutishna; Syiem, Donkupar; Bhan, Surya (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The aim of the present study is to determine the effects of Phlogacanthus thyrsiflorus on hyperglycemia and oxidative stress in kidneys of diabetic mice. Methods: Aqueous flower extract (AFE) and methanolic flower extract (MFE) were prepared. Preliminary phytochemical screenings were carried out. Diabetic mice were prepared by administering alloxan at 150 mg/kg body weight (b.w). The effects of different doses (150–550 mg/kg b.w) of the MFE on hyperglycemia were examined for short-term duration in diabetic mice. Activities of antioxidant enzymes, superoxide dismutase (CuZn-SOD and Mn-SOD), catalase (CAT), and glutathione reductase (GR) were examined under normal, diabetic, and diabetic-treated groups. Histopathological studies were also carried out for the above groups. Results: It has been found that the flavonoids and tannins were strongly present in MFE and further in vivo studies with MFE were carried out. It has been also observed that 250 mg/kg b.w dose of MFE showed significant reduction of blood glucose level. The activities of SOD, CAT, and GR increased in diabetic mice treated with MFE. Histological studies showed that MFE could further halt the damage caused by oxidative stress and reduced tissue injuries in diabetic mice. Conclusion: MFE of P. thyrsiflorus has positive effects in alloxan-induced diabetic mice and could be potential candidate for the detailed molecular studies and management of diabetes.